Genre analysis - John M Swales (Cambridge Univ. Press, 1990)
The book examines and develops the three key concepts of discourse community, genre and language-learning task. It goes on to explore a number of research genres with particular emphasis on the research article. Finally, it presents case studies of non-native student writing and examples of genre-based teaching materials designed to develop students'communicative competence in academic settings